Seven-Day Continuous Abstinence Rate from Smoking at 1, 2, or 3 Years after the Use of Varenicline - Kim, Jin Se; Jang, Ju Young; Park, Eun Hye; Lee, Joo Young; Gu, Kang Mo; Jung, Jae Woo; Choi, Jae Chol; Shin, Jong Wook; Park, In Won; Choi, Byoung Whui; Kim, Jae Yeol (Tuberculosis and respiratory diseases, 2015)
Varenicline, a selective partial agonist/antagonist of the α4β2 nicotinic receptor, has proven effectiveness for smoking cessation by several randomized, controlled trials. Because few studies have evaluated the long-term efficacy of varenicline, we tried to evaluate the smoking status of varenicline users up to 3 years after the initial prescription of the drug. We interviewed varenicline users who were prescribed the drug from June 2007 to May 2010 by telephone, from June 2010 to May 2011. One-hundred and thirty-three of 250 varenicline users (53.2%) were available for the survey. Seven-day continuous abstinence from smoking was adhered to by 17 of 39 respondents (43.6%) at 1 year, and 11 of 36 (30.6%) and 19 of 58 (32.8%) at 2 and 3 years since the first use of varenicline, respectively. Compared to current smokers, successful quitters were older (55.0 years vs. 49.9 years, p=0.01), had better compliance to the 12-week course (27.7 vs. 9.3%, p=0.01), and had taken varenicline longer (10.1 vs. 5.9 weeks, p=0.01). Fifty-four of 71 current smokers (76.1%) were willing to stop smoking in the near future. The preferred ways to cease smoking were will-power (48.1%), varenicline (25.9%), nicotine replacement therapy (11.1%), and others (14.9%). Smokers should be encouraged to stick to the proven way for recommended period of time for successful cessation of smoking.